2008
DOI: 10.1002/rra.1215
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of cover and hydraulics on brown trout habitat selection patterns

Abstract: Habitat modelling results are extremely sensitive to the habitat suitability criteria (HSC) used in the simulations. HSCs are usually expressed as univariate habitat suitability curves, although such univariate approach has been long questioned, since overlooking interactions between hydraulic variables may misrepresent the complexity of fish behaviour in habitat selection. It could lead to adopt erroneous flow management decisions based on misleading results. Furthermore, the interactive effects of hydraulic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 109 publications
(42 reference statements)
4
53
0
2
Order By: Relevance
“…The highest number of entries occurred in the shear layers between the inflowing and outflowing water, where the most frequent velocities ranged between 0 and 0.2 m/s, reaching values up to 0.3 m/s. The distribution of the preferred velocities for the entry of the fish into the refuge corresponded to the distribution that has been observed for juvenile brown trout in rivers (Souchon et al 1989;Vismara et al 2001;Ayllón et al 2009). …”
Section: Location Of Fish Entries Into the Refugesupporting
confidence: 66%
“…The highest number of entries occurred in the shear layers between the inflowing and outflowing water, where the most frequent velocities ranged between 0 and 0.2 m/s, reaching values up to 0.3 m/s. The distribution of the preferred velocities for the entry of the fish into the refuge corresponded to the distribution that has been observed for juvenile brown trout in rivers (Souchon et al 1989;Vismara et al 2001;Ayllón et al 2009). …”
Section: Location Of Fish Entries Into the Refugesupporting
confidence: 66%
“…Studies in different regions that also develop bivariate and multivariate models approve the controlling role of depth as a hydraulic variable (Ayllon, Almodovar, Nicola, & Elvira, 2009;Vismara, Azzellino, Bosi, Crosa, & Gentili, 2001). Munoz-Mas et al (2016) study results on Salmo farioides showed that the large fish prefer low velocity and deep parts.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the ensemble model has potential to improve upon the predictive performance of all single-model SDMs [22,53]. Schweizer et al (2007) and Ayllón et al (2009) emphasized the mutual dependency between flow velocity and depth [7,9]. In this study, HSI was obtained using six species distribution models, which only considered V and D throughout simulations.…”
Section: Sdm-determined Suitability Of Habitat With Respect To Spatiamentioning
confidence: 99%
“…Mesohabitats and stream biota have been shown to be associated with distinct combinations of current velocity and water depth [7]. Some studies have elucidated the correlation between current velocity and depth [7,8], as well as their combined effects in ecological modeling and assessment [9]. Additionally, these two variables are used in species distribution models (SDMs) to estimate HSI values for fish species.…”
Section: Introductionmentioning
confidence: 99%